A conceptual model to assess stress‐associated health effects of multiple ecosystem services degraded by disaster events in the Gulf of Mexico and elsewhere. Issue 1 (21st March 2017) - Sandifer, Paul A.; Knapp, Landon C.; Collier, Tracy K.; Jones, Amanda L.; Juster, Robert‐Paul; Kelble, Christopher R.; Kwok, Richard K.; Miglarese, John V.; Palinkas, Lawrence A.; Porter, Dwayne E.; Scott, Geoffrey I.; Smith, Lisa M.; et al.
Abstract: Few conceptual frameworks attempt to connect disaster‐associated environmental injuries to impacts on ecosystem services (the benefits humans derive from nature) and thence to both psychological and physiological human health effects. To our knowledge, this study is one of the first, if not the first, to develop a detailed conceptual model of how degraded ecosystem services affect cumulative stress impacts on the health of individual humans and communities. Our comprehensive Disaster‐Pressure State‐Ecosystem Services‐Response‐Health model demonstrates that oil spills, hurricanes, and other disasters can change key ecosystem components resulting in reductions in individual and multiple ecosystem services that support people's livelihoods, health, and way of life. Further, the model elucidates how damage to ecosystem services produces acute, chronic, and cumulative stress in humans which increases risk of adverse psychological and physiological health outcomes. While developed and initially applied within the context of the Gulf of Mexico, it should work equally well in other geographies and for many disasters that cause impairment of ecosystem services. Use of this new tool will improve planning for responses to future disasters and help society more fully account for the costs and benefits of potential management responses. The model also can be used to help direct investments in improving response capabilities of the public health community, biomedical researchers, and environmental scientists. Finally, the model illustrates why the broad range of potential human health effects of disasters should receive equal attention to that accorded environmental damages in assessing restoration and recovery costs and time frames. Key Points: We present a Disaster‐Pressure State‐Ecosystem Services‐Response‐Health framework linking disaster‐degraded ecosystem services to health Damaged ecosystem services produce acute, chronic, and cumulative stress that are associated with adverse health outcomes in humans Disaster‐related health effects deserve more attention in planning for future disasters and improving response and restoration efforts